Reactive oxygen species mediated apoptotic death of colon cancer cells: therapeutic potential of plant derived alkaloids - Nelson, Vinod K.; Nuli, Mohana Vamsi; Mastanaiah, Juturu; Saleem T. S., Mohamed; Birudala, Geetha; Jamous, Yahya F.; Alshargi, Omar; Kotha, Kranthi Kumar; Sudhan, Hari Hara; Mani, Ravishankar Ram; Muthumanickam, Alagusundaram; Niranjan, Divya; et al. (Frontiers in Endocrinology, 2023)
Colorectal cancer (CRC) is one of the most deaths causing diseases worldwide. Several risk factors including hormones like insulin and insulin like growth factors (e.g., IGF-1) have been considered responsible for growth and progression of colon cancer. Though there is a huge advancement in the available screening as well as treatment techniques for CRC. There is no significant decrease in the mortality of cancer patients. Moreover, the current treatment approaches for CRC are associated with serious challenges like drug resistance and cancer re-growth. Given the severity of the disease, there is an urgent need for novel therapeutic agents with ideal characteristics. Several pieces of evidence suggested that natural products, specifically medicinal plants, and derived phytochemicals may serve as potential sources for novel drug discovery for various diseases including cancer. On the other hand, cancer cells like colon cancer require a high basal level of reactive oxygen species (ROS) to maintain its own cellular functions. However, excess production of intracellular ROS leads to cancer cell death via disturbing cellular redox homeostasis. Therefore, medicinal plants and derived phytocompounds that can enhance the intracellular ROS and induce apoptotic cell death in cancer cells via modulating various molecular targets including IGF-1 could be potential therapeutic agents. Alkaloids form a major class of such phytoconstituents that can play a key role in cancer prevention. Moreover, several preclinical and clinical studies have also evidenced that these compounds show potent anti-colon cancer effects and exhibit negligible toxicity effects towards the normal cells. Hence, the present evidence-based studyreview aimed to provide an update on various alkaloids that have been reported to induce ROS-mediated apoptosis in colon cancer cells via targeting various cellular components including hormones and growth factors, which play a role in metastasis, angiogenesis, proliferation, and invasion. This studyreview also providesgives an individual account on each such alkaloid that underwent clinical trials either alone or in combination with other clinical drugs. In addition, we also discuss various classes of phytochemicals that induce ROS-mediated cell death in different kinds of cancers including colon cancer are discussed.